Theoretical assessment of using ceramic tiles as replacement of Ordinary Portland Cement and sand. Issue 1 (March 2021) - Joudah, Zahraa H; Hewayde, Esam; Samadi, Mostafa; Huseien, Ghasan F
Abstract: Using of industrial wastes as replacement of cement and/or other components of concrete is very attractive in concrete industry especially when this replacement leads to a reduction in the cost of concrete. This study investigates the feasibility of using two forms of ceramic tile wastes, naming: waste ceramic powder (WCP) and ceramic fine aggregate (CFA) as replacement of ordinary Portland cement (OPC) and river sand (RS), respectively. Twelve mortar mixtures incorporating various dosages of WCP and/or CFA were prepared to compare Carbone dioxide (CO2) emission, cost effectiveness, and energy consumption of the different mortar mixtures. Results showed that the use of WCP as replacement of OPC significantly reduces the CO2 emission, cost effective and energy consumption of the mortar mixtures. A replacement of 60% by weight of OPC by WCP resulted in a reduction of approximately 50%, 40% and 30% in CO2 emission, energy consumption, and cost respectively. The replacement of RS by different levels of CFA (up to 100%) had a marginal influence on the CO2 emission and energy consumption, while it moderately decreased the effective cost of the mortar mixtures. Results of using WCP as a partial replacement of cement are very encouraging and should be gathered with laboratory results about the effect of the replacement on properties of concrete to have a clear vision about selecting the appropriate materials of replacement for cement.